Pengembangan Ekowisata Berbasis Masyarakat Di Desa Pemo Taman Nasional Kelimutu Kabupaten Ende - Yudha Eka Nugraha; Yasinta Etrisia Siti (JURNAL DESTINASI PARIWISATA, 2020)
This research is concerned to elaborate new potential tourist attraction in Desa Pemo Taman Nasional Kelimutu. Desa Pemo has special attraction that is authentic and unique related with nature and culture. The method used is qualitative with descriptive approach. The data collected through in depth interviews with Head of Desa Pemo, Representative of Taman Nasional Kelimutu management, community member, and tourist. The data analyzed using IFAS EFAS analysis and SWOT analysis. The result shows that Desa Pemo has a authentic and unique attraction from the beauty of nature, culture, and hospitable community. Desa Pemo is classified in Quadrant I which means needs to take advantage of external opportunities, overcome internal weaknesses and avoid external threats. Keywords: Development Strategy, SWOT Analysis, Community-Based Ecotourism